MOLECULAR IDENTIFICATION TOOLS FOR BIVALVES: A REVIEW - MATHEW, ANIT ANNAMMA; AMPILI, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The Bivalvia class constitute an important molluscan class that exert its effect on human society an important food component and sentinel organism indicating environmental contamination. Accurate species identification is a prerequisite for management of aquaculture, diversity studies and for human consumption. Presence of different species of bivalves on the global markets for human consumption has given rise to several commercial frauds based on species substitution. Reliable and rapid techniques are required to identify seafood species in different products and thus prevent wilful or unintentional fraudulence. This article reviews the molecular tools used by different researchers in the last two decades. By reviewing virtually all genetic markers used during the last two decades of bivalve molecular research, it is obvious that the best tools for bivalve molecular study are mitochondrial COI and nuclear ITS2.